Network ties and export propensity of Vietnamese small and medium enterprises. Issue 1 (1st January 2019) - Nguyen, Huong T.X.; Le, Viet
ABSTRACT: This paper investigates the impacts of different network ties on export propensity of Vietnamese small and medium enterprises (SMEs) in the manufacturing sector. Using data from a survey of over 2, 600 manufacturing SMEs in 2015, we found that social networks contribute positively to the export propensity of SMEs, while the size of business networks negatively associates with the likelihood of export. However, bank networks and political networks are not significant for the propensity to export of Vietnamese SMEs. We discuss the results in detail and offer recommendations for SME owners, managers and policy makers.